복합발전플랜트 내의 가스 화재 거동에 관한 수치해석 - 박재용; Jae Yong Park; 성건혁; Kun Hyuk Sung; 이용남; Long Nan Li; 최진욱; Jin Wook Choi; 김대중; Dae Joong Kim; 이성혁; Seong Hyuk Lee; et al. (한국분무공학회지, 2015)
To date, the demand for Combined Cycle Power Plant (CCPP) has been continuously increased to overcome the problem of air pollution and lack of energy. In particular, the underground CCPP is exposed to substantial fire and explosion risks induced by gas leakage. The present study conducted numerical simulations to examine the fire behavior and gas leakage characteristics for a restricted region including gas turbine and other components used in a typical CCPP system. The com- mercial code of FLUENT V.14 was used for simulation. From the results, it was found that flammable limit distribution of leakage gas affects fire behavior. Especially, the flame is propagated in an instant in restricted region with LNG gas. In addi- tion, consequence analysis factors such as critical temperature and radiation heat flux are introduced. These results would be useful in making the safety guidelines for the underground CCPP.